1990
DOI: 10.1007/bf01314358
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and physiology of saxitoxin production by the dinoflagellatesAlexandrium spp.

Abstract: Toxin content (fmol cell-1) and a suite of elemental and macromolecular variables were measured in batch cultures of the dinoflagellates Alexandrium fundyense, A. tamarense and Alexandrium sp. from the southern New England region, USA. A different perspective was provided by semicontinuous cultures which revealed sustained, steady-state physiological adaptations by cells to N and P limitation. Two types of variability were investigated. In batch culture, changes in nutrient availability with time caused growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
248
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(278 citation statements)
references
References 25 publications
23
248
0
4
Order By: Relevance
“…3). In addition, our results showed that the cellular toxin content was higher under lower phosphate conditions, which was also documented by other studies (Boyer et al, 1987;Anderson et al, 1990;Maestrini et al, 2000;Guisande et al, 2002;Frangó -pulos et al, 2004).…”
Section: Toxin Content Change By Supplementationsupporting
confidence: 92%
See 1 more Smart Citation
“…3). In addition, our results showed that the cellular toxin content was higher under lower phosphate conditions, which was also documented by other studies (Boyer et al, 1987;Anderson et al, 1990;Maestrini et al, 2000;Guisande et al, 2002;Frangó -pulos et al, 2004).…”
Section: Toxin Content Change By Supplementationsupporting
confidence: 92%
“…However, the dinoflagellate species produce a high amount of toxins under nutrient limitation. Enhanced toxin production has been observed in PSP producers under phosphorus limitation (Boyer et al, 1987;Anderson et al, 1990;Maestrini et al, 2000;Guisande et al, 2002;Frangó pulos et al, 2004) and in other toxic species under nitrogen and phosphorus limitation (Johansson and Granéli, 1999). The toxin production is a compensatory strategy to minimize the competitive disadvantages of dinoflagellates under nutrient limitation (Frangó pulos , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of voltage-activated Na + or Ca 2+ channels could provide a link between ion transport and brevetoxin production; however, further research is needed to identify the presence of voltage-activated channels in dinoflagellates. It is important to note that similar studies with another toxic dinoflagellate, Alexandrium fundyense, found that osmotic stress did not influence toxin production (38), which suggests that osmoregulation may differ among dinoflagellate groups.…”
Section: Discussionmentioning
confidence: 99%
“…. The degree to which nutrient limitation effects cellular toxicity during natural blooms is unknown, but toxin production and content have been shown to decrease in nitrogen stressed laboratory cultures (Boyer et al 1985;Anderson et al 1990a;Anderson et al 1990b;.…”
Section: Allocation Of Carbon and Nitrogenmentioning
confidence: 99%